Relación entre el PH salival y la prevalencia de caries dental en escolares de 6 a 12 años de la institución educativa San Gabriel, Villa María del Triunfo, 2017 - Araujo Muro, Carlos Alberto (2019)
Objective: To determine the relationship between salivary pH and the prevalence of dental caries in schoolchildren aged 6 to 12 years in the city of Lima. Methodology: Cross-sectional study developed in 129 schoolchildren of the San Gabriel educational institution, in the district of Villa María del Triunfo, in 2017. Salivary pH measurements were obtained in the patients through the use of the pH-meter, assisted by strips of paper and the presence of dental caries was evaluated using the CPO-D method. The characteristics of sex and age of all patients were also evaluated. The statistics used the Chi-square tests and a significance level of p < 0.05 was used. Results: A prevalence of dental caries of 85.3% was found in schoolchildren between 6 and 12 years of age. The prevalence of caries according to gender was 45.7% in girls and 39.5% in boys. No statistically significant association was found between gender and the prevalence of dental caries (p = 0.935). 55% of the sample group presented an acid pH; 41.1%, a neutral pH, and 3.9%, an alkaline pH. The existence of a statistically significant association between salivary pH and dental caries (p<0.001) was determined. Conclusions: There is a direct relationship between salivary pH and the prevalence of dental caries. It was estimated that 95.8% of patients with acid salivary pH had dental caries.